Creative Economy Education Towards Family Food Security in the Jungsari Karanganyar Community - Siti Fatimah; Ahmad. M Fuadi; Dedi Gunawan (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Jungsari Village is one of the villages in the Karanganyar area, with geographical conditions located in a mountain valley. Access to urban areas is about 5 km. The majority of the professions of the Jungsari community are farmers and housewives. This condition spurred a touch of innovation to improve the family economy and food security. The purpose of this service activity is to provide education to the Jungsari community to make hand soap using materials available in the surrounding environment and cassava processed innovations. This pandemic period makes people have to care about hand hygiene to minimize the presence of the COVID-19 virus. After the community was given education on making hand soap, and various processed cassava, the community was also taught how to market online so that it would increase family income. This activity can be a side activity apart from being a farmer.